A rapid survey technique for tropilaelaps mite (Mesostigmata: Laelapidae) detection - Jeffery S. Pettis (2018)
Parasitic Tropilaelaps (Delfinado and Baker) mites are a damaging pest of European honey bees (Apis mellifera L.) in Asia. These mites represent a significant threat if introduced to other regions of the world, warranting implementation of Tropilaelaps mite surveillance in uninfested regions. Current Tropilaelaps mite-detection methods are unsuitable for efficient large scale screening. We developed and tested a new bump technique that consists of firmly rapping a honey bee brood frame over a collecting pan. Our method was easier to implement than current detection tests, reduced time spent in each apiary, and minimized brood destruction. This feasibility increase overcomes the test's decreased rate of detecting infested colonies (sensitivity; 36.3% for the bump test, 54.2% and 56.7% for the two most sensitive methods currently used in Asia). Considering this sensitivity, we suggest that screening programs sample seven colonies per apiary (independent of apiary size) and 312 randomly selected apiaries in a region to be 95% sure of detecting an incipient Tropilaelaps mite invasion. Further analyses counter the currently held view that Tropilaelaps mites prefer drone bee brood cells. Tropilaelaps mite infestation rate was 3.5 ± 0.9% in drone brood and 5.7 ± 0.6% in worker brood. We propose the bump test as a standard tool for monitoring of Tropilaelaps mite presence in regions thought to be free from infestation. However, regulators may favor the sensitivity of the Drop test (collecting mites that fall to the bottom of a hive on sticky boards) over the less time-intensive Bump test.